Baicalin Inhibits Influenza A Virus Infection via Promotion of M1 Macrophage Polarization - Geng, Ping; Zhu, Haiyan; Zhou, Wei; Su, Chang; Chen, Mingcang; Huang, Chenggang; Xia, Chengjie; Huang, Hai; Cao, Yiou; Shi, Xunlong (Frontiers in Pharmacology, 2020)
Background and Aims The natural compound baicalin (BA) possesses potent antiviral properties against the influenza virus. However, the underlying molecular mechanisms of this antiviral activity and whether macrophages are involved remain unclear. In this study, we, therefore, investigated the effect of BA on macrophages. Methods We studied macrophage recruitment, functional phenotypes (M1/M2), and the cellular metabolism via flow cytometry, qRT-PCR, immunofluorescence, a cell culture transwell system, and GC-MS–based metabolomics both in vivo in H1N1 A virus-infected mice and in vitro. Results BA treatment drastically reduced macrophage recruitment (CD11b+, F4/80+) by approximately 90% while maintaining the proportion of M1-polarized macrophages in the bronchoalveolar lavage fluid of infected mice. This BA-stimulated macrophage M1 phenotype shift was further verified in vitro in ANA-1 and primary peritoneal macrophages by measuring macrophage M1 polarization signals (CD86, iNOS, TNF-α, iNOS/Arg-1 ratio, and IL-1β cleavage). Meanwhile, we observed an activation of the IFN pathway (upregulation of IFN-β and IRF-3), an inhibition of influenza virus replication (as measured by the M gene), and distinct cellular metabolic responses in BA-treated cells. Conclusion BA triggered macrophage M1 polarization, IFN activation, and other cellular reactions, which are beneficial for inhibition of H1N1 A virus infection.